Carotenoid diversity in tropicaladapted yellow maize inbred lines - Menkir, A.; Liu, W.; White, W.S.; Maziya-Dixon, B.B.; Rocheford, T. (Elsevier, 2008)
Maize is a staple food for millions of people in sub-Saharan Africa where a significant number of people suffer from vitamin A deficiency. Yellow maize contains both pro-vitamin A and nonprovitamin A carotenoids with potential health benefits to humans. An improvement in the concentration of these compounds can have a positive impact on dietary intakes in areas where yellow maize is consumed. An essential first step in breeding yellow maize for enhanced carotenoid concentrations involves an assessment of the carotenoid diversity of adapted maize inbred lines. Trials were thus conducted (i) to explore the genetic variation in carotenoid concentrations among tropical-adapted yellow maize inbred lines, (ii) to assess the potential for concurrent improvement of different carotenoids and (iii) to determine the consistency of carotenoid concentrations in different locations. Seed samples of a large set of lines harvested from four trials grown in one location and a fifth trial grown in two locations were analyzed for carotenoid concentrations using HPLC. The analyses of variance revealed that carotenoid concentrations were not strongly affected by the differences in replications or locations. There were large differences among the tropical-adapted yellow maize inbred lines in lutein, zeaxanthin, β-carotene, β-cryptoxanthin, α-carotene and total pro-vitamin A contents. As significant correlations were observed among carotenoids sharing a single branch of the carotenoid biosynthetic pathway, it should be feasible to increase the levels of multiple carotenoids simultaneously. Principal component analysis on the carotenoid composition of the yellow inbred lines identified some lines with higher levels of all carotenoids formed across both major branches of the carotenoid biosynthetic pathway, and other lines having higher levels of those carotenoids formed under a single major branch of the carotenoid biosynthetic pathway. These indicate that the selection of parental lines with diverse carotenoid profiles may possibly be exploited for genetic improvement of carotenoids in tropical maize.